The SDGs of Education and Health Sector in Pakistan: Post Devolution Implementation Issues and Way Forward for Pakistan - Junejo, Asmatullah (Journal of Pakistan Administration, 2023)
The state of human development varies in every region of the world. Due to traditional and historic disparities, people inhabiting one part of the world can and do have lesser access to educational and health facilities and socio-economic opportunities as compared to people inhabiting other areas. In order to ensure that “no one is left behind‟ in terms of human development, the United Nations launched the Sustainable Development Goals (SDGs) in 2015. The global implementation of these 17 goals is being carried out with the help of the member states. Being one of the initial signatories of the SDGs, Pakistan had also committed to implementing the SDGs in the country. Hence while the commitment was made by the federal government of Pakistan in 2016, yet the provinces are also bound to honor the commitment of the federal government in terms of implementing the SDGs. This is in spite of the fact that all the subjects included in the SDGs pertain to the provincial governments in the post 18th constitutional amendment devolution. By way of its international commitment Pakistan is bound to implement UNSDGs. Therefore, there are some crucial social, economic and legal challenges that impede the implementation of the SDGs in the provinces in the post devolution environment. Although all the 17 SDGs are important, socially Goal # 3 relating to health and Goal # 4 relating to education are the most important. Hence, this research paper endeavors to explain the post devolution challenges in the implementation of these two goals. The present study explores the way forward for ensuring the quality education and health condition in Pakistan. However, all these challenges and impediments were overcome by undertaking suitable measures at both the provincial and federal levels in Pakistan. Dataset is taken from Economic Survey of Pakistan 2021-22 (Government of Pakistan, n.d.).  With the help of synergetic relationship between all the stakeholders, Pakistan could effectively achieve the target of sustainable development thereby leaving no one behind in the overall development process.
Keywords: Health; Education; SDG; Government